The impact that an accounting consultancy generates on the undertaking of former FARC excombatants in Colombia - Castro - Alarcón, Neidy Tatiana; López - Lizarazo, Yeimy Mayerly; Díaz -Rodríguez, Karen Yulien (Universidad Francisco de Paula Santander, 2020)
This article analyzes the need for accounting training in the enterprises of former FARC-EP combatants and projects its impact on cooperative projects. The objective is to contribute from the accounting area to provide former combatants with the necessary tools to financially manage their enterprises and thus ensure their permanence and growth; For this work a mixed investigation was carried out, in which a bibliographic review was made and also an instrument was applied to a representative sample of twenty enterprises, information with which it was possible to establish the need for accounting advice, the focus of the analysis is triangular. The main result is that most of the ex-combatants interviewed have not received accounting advice, and therefore do not have the knowledge to interpret financial information.